A rare cause of postpartum vaginal bleeding - Oğuzhan Tokur (SpringerOpen, 2021)
Abstract Background Invasive mole is a trophoblastic disease (GTD) caused by trophoblast cells invading the myometrium during pregnancy. The GTD range also includes mole hydatidiform, choriocarcinoma, and placental site trophoblastic tumor (PSTT). Invasive moles are most common following molar pregnancies; however, they can even rarely occur after a full-term birth. Despite the fact that pathology is the only way to make a clear diagnosis, clinic and radiologic evaluation can be helpful. We wanted to highlight a rare incidence of invasive mole following a healthy full-term delivery in this case. Case presentation A 28-year-old female patient presented with intermittent prolonged severe vaginal bleeding for 2 weeks after a term healthy vaginal delivery. In workup, beta human chorionic gonadotropin levels (b-hCG) value was 7540 mIU/ml. After suspicion of gestational trophoblastic neoplasm (GTN), the patient was sent to ultrasonography (US) and magnetic resonance imaging (MRI). GTN was confirmed by radiological and clinical findings, and a conclusive diagnosis of an invasive mole was made histopathologically. Conclusion Invasive mole should be considered in the differential diagnosis in patients with postpartum bleeding and a persistently high b-hCG level after a healthy term delivery.